The contribution of road‐based citizen science to the conservation of pond‐breeding amphibians. Issue 4 (23rd January 2019) - Sterrett, Sean C.; Katz, Rachel A.; Fields, William R.; Campbell Grant, Evan H.
Abstract: Roadside amphibian citizen science (CS) programmes bring together volunteers focused on collecting scientific data while working to mitigate population declines by reducing road mortality of pond‐breeding amphibians. Despite the international popularity of these movement‐based, roadside conservation efforts (i.e. "big nights, " "bucket brigades" and "toad patrols"), direct benefits to conservation have rarely been quantified or evaluated. As a case study, we used a population simulation approach to evaluate how volunteer intensity, frequency and distribution influence three conservation outcomes (minimum population size, population growth rate and years to extinction) of the spotted salamander ( Ambystoma maculatum ), often a focal pond‐breeding amphibian of CS and conservation programmes in the United States. Sensitivity analysis supported the expectation that spotted salamander populations were primarily recruitment‐driven. Thus, conservation outcomes were highest when volunteers focused on metamorph outmigration as opposed to adult in‐migration—contrary to the typical timing of such volunteer events. Almost every volunteer strategy resulted in increased conservation outcomes compared to a no‐volunteer strategy. Specifically, volunteer frequency during metamorph migration increased outcomes more than the same increases in volunteer effort during adult migration. Small population sizes resulted in a negligible effect of volunteer intensity. Volunteers during the first adult in‐migration had a relatively small effect compared to most other strategies. Synthesis and applications . Although citizen science (CS)‐focused conservation actions could directly benefit declining populations, additional conservation measures are needed to halt or reverse local amphibian declines. This study demonstrates a need to evaluate the effectiveness of focusing CS mitigation efforts on the metamorph stage, as opposed to the adult stage. This may be challenging, compared to other management actions such as road‐crossing infrastructure. Current amphibian CS programmes will be challenged to balance implementing evidence‐based conservation measures on the most limiting life stage, while retaining social and community benefits for volunteers. Abstract : Although citizen science (CS)‐focused conservation actions could directly benefit declining populations, additional conservation measures are needed to halt or reverse local amphibian declines. This study demonstrates a need to evaluate the effectiveness of focusing CS mitigation efforts on the metamorph stage, as opposed to the adult stage. This may be challenging, compared to other management actions such as road‐crossing infrastructure. Current amphibian CS programmes will be challenged to balance implementing evidence‐based conservation measures on the most limiting life stage, while retaining social and community benefits for volunteers.